As propensões da evasão, no período da pandemia, no curso de Administração de uma faculdade privada do oeste do Paraná - Casagrande, Edineia (2021)
This research analyzed evasion propensities in private higher education, in the period of the COVID-19 pandemic in the year 2020, in a college located in western Paraná. In this investigation, quantitative data from an electronic questionnaire were used and the sample was composed of 93 academics. The qualitative methodology was also used through the tools Swot Analysis and Porter's five forces. The information was collected by means of interviews with the management and strategic team of the Higher Education Institutions (HEI). The questionnaire data were analyzed by descriptive statistics and by means of the Structural Equation Modeling (SEM) technique, using the Partial Least Squares (PLS) method, with the use of the SmartPLS 3.3.3 software. Based on the strategic planning developed, the actions proposed to improve the management of the institution's evasion propensity were elaborated and, by means of a reflective model, the results of the questionnaire carried out show that economic, pedagogical practices, social complexity, time, and course structure issues are important dimensions of the evasion propensity in private higher education, in the pandemic period of the year 2020, at the studied HEI. We cannot fail to mention the environmental issue, an important variable in the times in which we live; people with low education tend to have less information and therefore less environmental awareness, which can cause major social impacts. Thus, it is important to promote people-oriented development, a breakthrough that provides real improvements in the quality of human life; otherwise, it will be a problem that society and government will have to face. Therefore, this study enhances comprehension and contributes to the literature by understanding evasion in private higher education in the pandemic of Covid-19 in the year 2020.